(untitled) (Euro-Asia Conferences, 2021)
The creator has a unique personality. The psychology of artistic creation, the process of creation and the environment of the creative nature has been studied in depth in foreign literature [1]. It is also one of the most important issues in Uzbek literature [2]. The views of Uzbek enlightened artists in this regard are also unique. Especially, Abdulla Qodiriy’s literary-theoretical views on creative responsibility, the creative process, the choice and application of imagery are noteworthy.